The Quay Brothers : into a metaphysical playroom - Buchan, Suzanne (University of Minnesota Press, 2011)
"This work is the first thorough analysis of the creative oeuvre of the Quay Brothers. Known for their animation shorts that rely on puppetry, miniatures, and stop-motion techniques, their fiercely idiosyncratic films are fertile fields for Suzanne Buchan's engaging descriptions and provocative insights into the Quays' art-and into the art of independent puppet animation. Buchan's aesthetic investigation stems from extensive access to the Quay Brothers' artistic practices and work, which spans animation and live-action film, stage design and illustration. She also draws on a long acquaintance with them and on interviews with collaborators essential to their productions, as well as archival sources. Discussions of their films' literary origins, space, puppets, montage, and the often-overlooked world of sound and music in animation shed new light on the expressive world that the Quay Brothers generate out of their materials to create the poetic alchemy of their films. At once a biography of the Quays' artistic trajectory and a detailed examination of one of their best-known films, Street of Crocodiles, this book goes further and provides interdisciplinary methodologies and tools for the analysis of animation"--Provided by publisher